Figures of Edgar Allan Poe : authorship, antebellum literature, and transatlantic rhetoric - Guttzeit, Gero (Berlin : De Gruyter, 2017)
The Anglia Book Series (ANGB) offers a selection of high quality work on all areas and aspects of English philology. It publishes book-length studies and essay collections on English language and linguistics, on English and American literature and culture from the Middle Ages to the present, on the new English literatures, as well as on general and comparative literary studies, including aspects of cultural and literary theory.
4 The Genius Rhetorician: The Rhetoric of "The Philosophy of Composition"5 "The Ingenuity of Unravelling": Abductive Powers and Rhetorical Inventors in the Tales of Ratiocination; 6 The Jingle-Man and the Damned Rhetorician: Poetry, Elocution, and the Political Rationale of Verse; 7 "The Only Proper Stage for the Literary Histrio": Delivery and its Dangers in the Antebellum Cultures of Rhetoric and Print; Concluding Remarks; Works Cited; Index of Names; Index of Subjects.
Includes bibliographical references and indexes.
eBooks on EBSCOhost
Keywords: Poe, Edgar Allan, -- 1809-1849 -- Criticism and interpretation; Poe, Edgar Allan, -- 1809-1849; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; 19th-Century American Literature; Depiction of Literary Characters; Edgar Allan Poe; Academic Dissertation; dissertations; Academic theses; Criticism, interpretation, etc; Academic theses; Thèses et écrits académiques.